Giant Parasagittal Meningioma with Complete Visual Loss in Young Female: A Case Report - Sinaga, Patrice LWY; Irsyad, Muhammad Ari; Dharmajaya, Ridha (Fakultas Kedokteran Universitas Brawijaya, 2021)
Parasagittal meningioma is a benign extra-axial tumor from the arachnoid cap cell that fills the parasagittal angle. This case report presents a case of a 21-years old young female with a history of complete visual loss, left side paresthesia, and progressive blunt headache. Brain MRI and MRV revealed a giant enhancing tumor measuring 9.2 cm x 8.41 cm x 7.5 cm on the right parietooccipital lobe with obstruction of the posterior third of the superior sagittal sinus. Gross total removal was achieved. The pathology reports confirmed a WHO grade I meningioma. The paresthesia and headache were improved, but the loss of visions did not change. Giant parasagittal meningioma may invade the superior sagittal sinus leading to intracranial hypertension. The surgical strategy should target the survival and postoperative quality of life. Occlusion of posterior third superior sagittal sinus affects deficiency venous return resulting in visual loss.